2018
DOI: 10.1111/jog.13757
|View full text |Cite
|
Sign up to set email alerts
|

Low serum folate status in the second trimester increase the risk of low birthweight in Chinese women

Abstract: Low serum folate levels in the second trimester significantly increases the risk of LBW amongst Chinese women with singleton pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, although a previous meta-analysis ( 4 ) revealed that consuming FA supplements during periconception or early pregnancy could reduce the risk of ASD in offspring, emerging evidence shows that low plasma/serum folate concentration in the second and third trimesters of pregnancy is also likely associated with increased risks of physical health issues (e.g., low birthweight) ( 32 ) and cognitive development (e.g., language development) in offspring ( 33 , 34 ). Folate plays an essential role in DNA methylation as a provider of methyl groups ( 6 ), which is considered crucial for the development of the central nervous system and is implicated in the formation of fundamental brain structures ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although a previous meta-analysis ( 4 ) revealed that consuming FA supplements during periconception or early pregnancy could reduce the risk of ASD in offspring, emerging evidence shows that low plasma/serum folate concentration in the second and third trimesters of pregnancy is also likely associated with increased risks of physical health issues (e.g., low birthweight) ( 32 ) and cognitive development (e.g., language development) in offspring ( 33 , 34 ). Folate plays an essential role in DNA methylation as a provider of methyl groups ( 6 ), which is considered crucial for the development of the central nervous system and is implicated in the formation of fundamental brain structures ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma folate, a transport form of folate to the tissue and to the fetus (6) , plays crucial roles in maintaining maternal and offspring health. Accumulating evidence shows that a low plasma or serum folate concentration in mid-to late pregnancy is likely associated with increased risks of pre-eclampsia (7) , preterm birth (8) , low birth weight (9) and poor language development in young children (10) . Animal models also showed that folate deficiency during lactation could alter cerebellar synapsin expression in offspring (11) .…”
mentioning
confidence: 99%